Disconnections between medical education and medical practice: A neglected dilemma. Issue 9 (1st September 2020) - Benatar, Solomon; Daneman, Denis
ABSTRACT: Medical practice has changed profoundly over the past 60 years. Many changes have also been made in medical education, often with a view to countering adverse aspects of highly specialised, commercialised and bureaucratised modern medical practice. Regardless of the state of the world today and of the variety of changes that may occur in the years ahead, excellence in the application of bedside skills and technological advances, accompanied by excellence in humanistic aspects of caring for patients as people, will remain preeminent goals at the heart of medical practice. Powerful social forces that negatively influence practice cannot be counteracted through changes in medical education alone and need to be addressed directly within health systems. Shifting healthcare towards a valued social service is arguably essential for improving both public and individual health through more widespread universal access to high quality and effectively integrated health care.